Researching extremists and terrorists: reflections on interviewing hard-to-reach populations - Carthy, Sarah L. (Fieldwork experiences in criminology and security studies, 2023)
Extremism continues to rank among the principal security concerns of Western states and societies in the twenty-first century. In the last several years, research on this subject has moved away from static constructs of perpetration and started to explore the phenomenon in a more complex way, including its different manifestations. Fieldwork in this area is no longer bound to the study of individuals who have conducted terrorist attacks, but also the larger group who legitimise and support extremist violence without engaging in it. However, accessing these populations presents particular challenges, especially as the field continues to develop and diversify. How do you gain access to populations who are defined by what they haven’t done? What interview techniques ensure candid responses? Does fieldwork in this area present unique ethical challenges and, if so, how can these be navigated? This chapter explores the reality of accessing and interviewing these hard-to-reach populations, drawing from the authors’ experiences across a number of projects on radicalisation, extremism, and terrorism.